(untitled) (Dermatology Reports, 2022)
Because of its higher level of safety compared to its parent medicine, thalidomide, lenalidomide (L) is chosen for the treatment of multiple myeloma. We report a patient who, within a month of using L, developed more than 10 basal cell carcinomas.